Exploring successes, barriers, and enablers in the one-year digital Healthy Weight Coaching - Anu Joki; Aila J. Ahola; Laura U. Suojanen; Kirsi H. Pietiläinen (BMC, 2024)
Abstract Introduction Healthcare professionals' perspectives are often overlooked in the evaluation of digital weight loss interventions. Thus, we examined how healthcare professionals perceive patient success in a one-year web-based weight management program, the Healthy Weight Coaching, aiming to identify key success factors and common challenges within the coaching process. Methods Thematic analysis was conducted on ten semi-structured interviews with healthcare professionals from the Healthy Weight Coaching. Interviewees included individuals of both sexes, with an average age of 41 years, ranging from 10 months to 5 years of coaching experience, and treating 90 to 500 patients. Results Three main themes emerged from the analysis: (1) Positive progress during the Healthy Weight Coaching, (2) Factors facilitating success, and (3) Barriers hindering progress. The coaches noted significant positive changes among patients, including increased self-compassion, reduced weight-related stress, and a shift toward holistic well-being. Improvements in eating habits, physical activity, and vegetable consumption were observed, along with reductions in binge eating behaviors. Personal factors such as internal motivation and engagement with the program were crucial for success. Additionally, aspects of the Healthy Weight Coaching program, such as its individualized and supportive environment, flexible coaching approach, and the pivotal role of coaches, were seen as facilitators of success. Patients valued being treated equally and acceptingly and fostering trust and collaboration. However, challenges such as burdensome life situations, limited resources, and inadequate support posed significant barriers to progress. Unrealistic goals and societal pressures were also observed to hinder successful weight management efforts. Conclusion A comprehensive, individualized approach addressing resource limitations and societal norms can enhance long-term success in weight management programs like the Healthy Weight Coaching, ultimately promoting overall well-being.